Quantifying the relationship between the climate and Hand-Foot-Mouth Disease (HFMD) incidences - Pei Fung, Leong; Jane, Labadin; Shapiee, Bin Abd Rahman; Sarah Flora, Samson Juan (2011)
This paper aims to examine the relationship between climate changes and Hand-Foot-Mouth Disease (HFMD) incidences. A study to examine the relationship between the weather and the HFMD cases in Sarawak, Malaysia had been done. However, the weather data obtained from the five meteorological stations in Sarawak were too few to represent the whole Sarawak, which account for unreliable results. To reach a better understanding of the effect of climate changes on the transmission of HFMD, this paper aims to quantify the relationship between climate changes and HFMD incidences in Singapore instead of Sarawak due to the smaller area of Singapore and the similar weather conditions for Singapore and Sarawak. The weather variables and incidences of HFMD during the period 2006-2008 had been collected on a weekly basis. The correlation analysis was conducted between weather variables and HFMD cases. Air temperature, pressure and wind speed were found to be significantly correlated with the number of HFMD cases in Singapore. This shows that weather variations may affect the transmission of HFMD in Singapore. It is suggested that air temperature could be used as a predictor of the number of HFMD cases in tropical countries. Thus, public health interventions should be conducted during this stage in order to adapt and overcome the possible affects of climate change in the future.